Facile size-controllable synthesis of single crystalline β-MnO2 nanorods under varying acidic strengths. Issue 9 (18th January 2016) - Kumar, Niraj; Dineshkumar, P.; Rameshbabu, R.; Sen, Arijit
Abstract : A simple one-pot hydrothermal synthesis of single crystalline β-MnO2 nanorods with diameters in the range of 10–40 nm is reported. Abstract : A simple one-pot hydrothermal synthesis of single crystalline β-MnO2 nanorods with diameters in the range of 10–40 nm is reported. During the synthesis process, the acid molarities were varied from 1.1 M down to 0.2 M in steps of 0.3 M while keeping the other reaction parameters constant, resulting in gradual transformation of the size of β-MnO2 from micro to the nanoscale dimension. The as synthesized nanorods exhibit soft ferromagnetic behavior and possess a high catalytic activity with an onset potential of −0.17 V in facilitating the oxygen reduction reaction (ORR).